Reliability evaluation method for welding process of ceramic substrate
By preparing unitized ceramic welding substrate samples and conducting a series of tests and analysis, a method for evaluating the reliability of ceramic substrate welding process is proposed, which solves the problem that the existing technology is difficult to effectively evaluate the reliability of ceramic substrate welding process, and achieves a more scientific and economical welding process evaluation.
Patent Information
- Application Number
- CN202311762571.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively evaluate the reliability of the ceramic substrate welding process, especially when considering the impact of porosity on welding strength during welding, the existing methods are costly, time-consuming and the data lacks general applicability.
A method for evaluating the reliability of ceramic substrate welding process is proposed. By preparing unitized ceramic welding substrate samples, shear strength test, fracture surface porosity analysis, high-temperature storage and temperature cycle aging, the shear attenuation curve is drawn, and the welding process evaluation factor is calculated to comprehensively evaluate the reliability of ceramic substrate welding process.
This method avoids a large number of repeated welding strength cycle experiments, reduces time and capital costs, provides new theoretical basis and innovative ideas for the reliability evaluation and prediction of ceramic substrate welding process, and can more scientifically judge the reliability of ceramic substrate welding process.
Smart Images

Figure CN119780394A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of reliability evaluation of a ceramic substrate welding process, and in particular to a method for evaluating the reliability of a ceramic substrate welding process. Background Art
[0002] Hybrid integrated circuit technology is an integrated circuit technology that uses thick film processes such as screen printing, drying, and sintering to make printed circuits on ceramic substrates and integrate active or passive devices on ceramic substrates. Due to the small number of solder joints, hybrid integrated circuits can be more reliably connected to more stable ceramic substrates than circuits formed by different components.
[0003] At present, thick film hybrid integrated circuit ceramic substrates are usually fixed on metal or ceramic shells by soldering, and it is difficult to evaluate the strength of the ceramic substrate welding process by testing. Because there are many parameters in the actual process of thick film hybrid integrated circuit welding, it is difficult to comprehensively evaluate the reliability of the ceramic substrate welding process through a single test. Evaluating the strength performance of the welding process has always been a challenging task. An existing method is to apply cyclic loads to a specific material until the life and strength are obtained, and finally draw the SN curve (Wohler curve). The disadvantages of this method are high cost, waste of time, and the data obtained lacks universal applicability to other different component materials and welding processes of thick film ceramic substrates. In addition, the above method does not consider the influence of porosity on the strength of the ceramic substrate welding process in the actual welding process for the thick film ceramic substrate welding process, and the evaluation error of the welding strength under different process parameters of the same solder is large. Therefore, it is impossible to evaluate and optimize the ceramic substrate welding process.
[0004] Considering the defects of the existing ceramic substrate welding process evaluation method, it is necessary to explore a new ceramic substrate welding process reliability evaluation method in order to more simply and comprehensively evaluate the welding performance of ceramic substrates under different process parameters. Summary of the invention
[0005] In order to solve the above problems, this application proposes a ceramic substrate welding process reliability evaluation method, which avoids a large number of time-consuming and labor-intensive welding strength cycle experiments, reduces time and money costs, and provides a new theoretical basis and innovative ideas for thick film ceramic substrate performance evaluation and process parameter optimization.
[0006] This application is implemented through the following technical solutions:
[0007] This application proposes a ceramic substrate welding process reliability evaluation method, comprising the following steps:
[0008] S1. Preparing unitized ceramic welding substrate samples: making pad patterns on the backs of multiple thick-film ceramic substrates, and welding the thick-film ceramic substrates with the pad patterns made thereon to a steel housing to obtain multiple unitized ceramic welding substrate samples;
[0009] S2. Obtaining the shear strength and fracture porosity of the unitized ceramic welded substrate samples: Perform horizontal shear force tests on some unitized ceramic welded substrate samples, record the shear force data J1 at this time, and perform height analysis on the sample cross section to record the porosity K of the cross section. n ;
[0010] S3, high temperature storage of unitized ceramic welding substrate samples: high temperature baking is performed on some of the remaining samples after S2 treatment, and the unitized ceramic welding substrate samples cooled to room temperature after high temperature storage are subjected to horizontal shear force test, and the shear force data J2 at this time is recorded;
[0011] S4. Temperature cycle aging of unitized ceramic welding substrate samples: some of the remaining samples after S3 treatment were placed in -65℃ for 30min, and then placed in 150℃ for 30min. The samples after insulation were subjected to temperature cycle aging at 50℃, 100℃, 150℃, and 200℃, respectively. Multiple samples were used for temperature cycle aging at each temperature. The unitized ceramic welding substrate samples cooled to room temperature after temperature cycle aging were subjected to horizontal shear force test to obtain multiple sets of shear force data, namely, J 50 , J 100 , J 150 , J 200 ;
[0012] S5. Draw the shear force attenuation curve of the unitized ceramic welding substrate sample: for J1, J2, J 50 , J 100 , J 150 and J 200 The average value of all data in each group is obtained The horizontal axis is the test number, and the vertical axis is Linear fitting gives the following formula:
[0013] J=ax+δ
[0014] Among them, δ represents the initial welding strength, and a represents that the welding strength decay rate is a negative value;
[0015] S6. Obtain the ceramic substrate welding process evaluation factor: According to the initial welding porosity and the initial welding strength, the following formula is obtained:
[0016]
[0017] Among them, σ represents the welding process evaluation factor. The larger the value of the welding process evaluation factor is, the higher the welding process reliability of the ceramic substrate is.
[0018] Furthermore, in step S1, the size of the thick film ceramic substrate is 2×2 mm.
[0019] Furthermore, in step S1, the pad pattern is a regular pattern, and the pad pattern includes but is not limited to a rectangle, a regular hexagon and a circle.
[0020] Further, in step S1, the steel shell includes but is not limited to No. 10 steel or Kovar alloy.
[0021] Furthermore, in step S1, the thick film ceramic substrate is welded to the steel housing by welding methods including but not limited to hot plate reflow and vacuum reflow.
[0022] Furthermore, in step S1, the number of unitized ceramic welding substrate samples is greater than 30.
[0023] Furthermore, in step S2, the number of samples tested for shear strength and fracture surface porosity is greater than 5.
[0024] Furthermore, in step S3, the high temperature baking condition is to place the sample in an environment with a temperature greater than 70% of the melting point of the solder and bake it at a high temperature for 30-168 hours.
[0025] Furthermore, in step S3, the number of samples stored at high temperature is greater than 5.
[0026] Further, in step S4, at least 5 samples are subjected to temperature cycle aging test at each temperature.
[0027] The beneficial effects of the present application are as follows: the present invention combines the ceramic substrate welding shear force test, the welding fracture surface porosity microscopic image test and the thermal stress aging treatment process to establish a quantitative relationship between the surface geometry of the ceramic substrate welding interface, the uneven material distribution and the reliability of the ceramic substrate welding process, comprehensively evaluates the reliability of the ceramic substrate welding process, avoids a large number of repetitive ceramic substrate welding process tests, reduces time and financial costs for enterprises, and provides a new theoretical basis and innovative ideas for the evaluation and prediction of the reliability of the ceramic substrate welding process. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the process of the present invention;
[0029] Figure 2 It is a schematic structural diagram of a square pad of the present invention;
[0030] Figure 3It is a schematic structural diagram of a circular pad of the present invention;
[0031] Figure 4 It is a schematic diagram of the structure of the hexagonal pad of the present invention;
[0032] Figure 5 A schematic diagram of a shear force attenuation curve of a sample in an example of the present invention is drawn;
[0033] Figure 6 It is a schematic diagram of the welding interface of the aluminum nitride substrate in an example of the present invention;
[0034] Figure 7 It is a schematic diagram of the welding interface of the aluminum oxide substrate in an example of the present invention. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0037] In addition, the descriptions of "first", "second", etc. in this application are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0038] This application proposes a ceramic substrate welding process reliability evaluation method, comprising the following steps:
[0039] S1. Preparation of unitized ceramic welding substrate samples.
[0040] Specifically, the size of the thick film ceramic substrate is 2×2 mm, and a pad pattern is made on the back of the pad by screen printing, wherein the pad pattern can be a regular pattern such as a rectangle, a regular hexagon, or a circle. Figure 2 As shown in the figure, the back of the unitized ceramic welding substrate sample is a square pad structure, the substrate pad size is a square with a side length of no more than 1.5mm, the distance between the pad and the edge of the substrate should be greater than 0.25-0.3mm, and the push knife should be parallel to the edge of the substrate during the horizontal shear force test. Figure 3 As shown in the figure, the back of the unitized ceramic welding substrate sample is a circular pad structure, the diameter of the substrate pad is a circle with a side length of no more than 1.5mm, the distance between the pad and the edge of the substrate should be kept between 0.25-0.3mm, and the push knife should be parallel to the edge of the substrate during the horizontal shear force test. Figure 4 As shown, the back of the unitized ceramic welding substrate sample is a regular hexagonal pad structure. The side length of the substrate pad is a regular hexagon with a side length not exceeding 0.9 mm. The distance between the pad and the edge of the substrate should be maintained between 0.1-0.3 mm. During the horizontal shear force test, the push knife should be kept parallel to both the substrate and the pad edge.
[0041] S2. Welding of unitized ceramic welding substrate samples.
[0042] Specifically, the unitized thick film ceramic welding substrate with the back pad is welded to the steel shell, wherein the steel shell can be No. 10 steel or Kovar alloy, and the welding method can include hot plate reflow and vacuum reflow, and the number of samples in this step is greater than 30.
[0043] S3. Shear strength and fracture surface porosity of unitized ceramic welded substrate samples.
[0044] Specifically, a thrust machine is used to test the horizontal shear force of a unitized thick film ceramic welding substrate sample that has just been cooled to room temperature after welding, and the shear force data J1 is recorded. A white light interferometer is used to perform a height analysis on the sample section, and the porosity K of each section is recorded. n , the number of samples tested in this step is greater than 5.
[0045] S4. High temperature storage of unitized ceramic welding substrate samples.
[0046] Specifically, the remaining samples after S3 treatment are placed in an environment with a temperature greater than 70% of the melting point of the solder and baked at a high temperature for 30-168 hours. The unitized thick film ceramic welding substrate samples that have just been cooled to room temperature after high temperature storage are subjected to a horizontal shear force test by a thrust machine, and the shear force data J2 at this time is recorded. The number of samples tested in this step is greater than 5.
[0047] S5. Temperature cycle aging of unitized ceramic welding substrate samples.
[0048] Specifically, the remaining samples after S4 treatment were placed in -65℃ for 30min and then placed in 150℃ for 30min. The samples were subjected to temperature cycle aging at 50℃, 100℃, 150℃ and 200℃ respectively. The unitized thick film ceramic welding substrate samples cooled to room temperature after temperature cycle aging were subjected to horizontal shear force test by a thrust machine, and the shear force data J at this time were recorded. 50 , J 100 , J 150 , J 200 In this step, the number of samples in each temperature cycle aging test interval is greater than 5.
[0049] S6. Drawing of shear force attenuation curve of unitized ceramic welding substrate sample.
[0050] Specifically, for J1, J2, J 50 , J 100 , J 150 , J 200 The average value of all data in each group is The horizontal axis is the test number, and the vertical axis is Linear fitting is performed to obtain J=ax+δ, where δ represents the initial welding strength taking into account the welding attenuation performance, a represents that the welding strength attenuation rate is a negative value, and the smaller the a value and the larger the |a| value, the faster the welding strength attenuation rate.
[0051] S7. Ceramic substrate welding process evaluation factors.
[0052] Specifically, the evaluation of the ceramic substrate welding process requires the initial welding porosity and the initial welding strength considering the welding attenuation performance, and then the following formula is obtained:
[0053]
[0054] After substituting the S1-S6 test parameters, the larger σ value of different welding processes of the ceramic substrate proves that the welding process reliability of the ceramic substrate is higher.
[0055] The final value of σ of this evaluation method represents the comprehensive comparison result of the initial welding strength of the ceramic substrate sample, the welding strength decay rate of the ceramic substrate sample, and the porosity of the welding interface of the ceramic substrate sample. It can make a more scientific judgment when evaluating the reliability of the ceramic substrate welding process.
[0056] Examples
[0057] The reliability of the welding process of AlN and alumina ceramic substrate with square back pads on No. 10 steel housing was evaluated using 62Sn36Pb2Ag solder at a welding temperature of 210°C. The specific steps are as follows:
[0058] 1. Preparation of unitized ceramic welding substrate samples: The thick film ceramic substrate is a square with a side length of 2mm. The pad pattern is made on the back of the pad by screen printing. The pad pattern on the back is a square of 1.5mm, and the distance between the pad and the edge of the substrate is kept at 0.25mm;
[0059] 2. Welding of unitized ceramic welding substrate samples: The unitized thick film ceramic welding substrate with the back pads made is hot plate welded on the No. 10 steel shell, and the welding thickness of the two sets of pad samples is 0.2mm;
[0060] 3. Shear strength and fracture porosity of unitized ceramic welded substrate samples: The unitized thick film ceramic welded substrate samples that have just been cooled to room temperature after welding are subjected to horizontal shear force test by a thrust machine, and the shear force data J1 is recorded. The sample cross section is highly analyzed by white light interferometer, and the porosity K of each cross section is recorded. n ,The number of test samples in this step is greater than 5, and the data records are shown in Table 1.
[0061] Table 1 Porosity data
[0062]
[0063] 4. High-temperature storage of unitized ceramic welding substrate samples: Place the remaining samples after processing in step 3 in an environment with a temperature greater than 70% of the melting point of the solder and bake them at a high temperature for 48 hours. Use a thrust machine to cool the unitized thick-film ceramic welding substrate samples that have just been cooled to room temperature after high-temperature storage to perform a horizontal shear force test, and record the shear force data J2 at this time. The number of samples tested in this step is greater than 5, and the data records are shown in Table 2.
[0064] Table 2 Test data
[0065]
[0066] 5. Temperature cycle aging of unitized ceramic welding substrate samples: Place the remaining samples after treatment in step 4 in a -65℃ environment for 30 minutes and then place them in a 150℃ environment for 30 minutes. The samples are cycle aged at 50℃, 100℃, 150℃, and 200℃ respectively. The unitized thick film ceramic welding substrate samples that have been cooled to room temperature after temperature cycle aging are tested for horizontal shear force by a thrust machine, and the shear force data at this time are recorded. 50 , J 100 , J 150 , J 200 The number of samples in each temperature cycle aging test interval of this step is greater than 5, and the data are recorded in Table 1;
[0067] 6. Drawing of shear force attenuation curve of unitized ceramic welding substrate samples: for J1, J2, J 50 , J100 , J 150 and J 200 The average value of all data in each group is obtained The horizontal axis is the test number, and the vertical axis is Linear fitting is performed to obtain J = ax + δ. The curve is as follows Figure 5 As shown in the figure, |a 氮化铝 |=16.46,|a 氧化铝 |=15.18,δ 氮化铝 =173.96,δ 氧化铝 =226.48.
[0068] 7. Ceramic substrate welding process evaluation factors: The evaluation of ceramic substrate welding process requires the initial welding porosity and the initial welding strength considering the welding attenuation performance, and then the following formula is obtained:
[0069]
[0070] After substituting the process test parameters from one to six, the larger the σ value of the different welding processes of the ceramic substrate, the higher the welding process reliability of the ceramic substrate. The results are shown in Table 3:
[0071] Table 3 Evaluation results
[0072]
[0073] The results show that when the alumina substrate is evaluated using 62Sn36Pb2Ag solder, the welding process reliability of the alumina ceramic substrate using a square back pad on a No. 10 steel shell is higher when the welding temperature is 210°C.
[0074] go through Figure 6 and Figure 7 In contrast, the welding interface of the alumina substrate has a lower porosity, which is consistent with the σ evaluation result.
[0075] Of course, the present application may have many other implementations. Based on the present implementation, other implementations obtained by ordinary technicians in this field without any creative work are all within the scope of protection of the present application.
Claims
1. A method for evaluating the reliability of a ceramic substrate welding process, characterized in that: The following steps are involved: S1. Preparing unitized ceramic welding substrate samples: making pad patterns on the back of a plurality of thick film ceramic substrates, and welding the thick film ceramic substrates with the pad patterns made thereon to a steel housing to obtain a plurality of unitized ceramic welding substrate samples; S2. Obtaining the shear strength and fracture porosity of the unitized ceramic welded substrate samples: Perform horizontal shear force tests on some unitized ceramic welded substrate samples, record the shear force data J1 at this time, and perform height analysis on the sample cross section to record the porosity K of the cross section. n ; S3, high temperature storage of unitized ceramic welding substrate samples: high temperature baking of some samples of the remaining samples after S2 treatment, horizontal shear force test of the unitized ceramic welding substrate samples cooled to room temperature after high temperature storage, and recording the shear force data J2 at this time; S4. Temperature cycle aging of unitized ceramic welding substrate samples: some of the remaining samples after S3 treatment were placed in -65℃ for 30min, and then placed in 150℃ for 30min. The samples after insulation were subjected to temperature cycle aging at 50℃, 100℃, 150℃, and 200℃, respectively. Multiple samples were used for temperature cycle aging at each temperature. The unitized ceramic welding substrate samples cooled to room temperature after temperature cycle aging were subjected to horizontal shear force test to obtain multiple sets of shear force data, namely, J 50 , J 100 , J 150 , J 200 ; S5. Draw the shear force attenuation curve of the unitized ceramic welding substrate sample: for J1, J2, J 50 , J 100 , J 150 and J 200 The average value of all data in each group is obtained The horizontal axis is the test number, and the vertical axis is Linear fitting gives the following formula: J=ax+δ Among them, δ represents the initial welding strength, and a represents that the welding strength decay rate is a negative value; S6. Obtain the ceramic substrate welding process evaluation factor: According to the initial welding porosity and the initial welding strength, the following formula is obtained: Among them, σ represents the welding process evaluation factor. The larger the value of the welding process evaluation factor is, the higher the welding process reliability of the ceramic substrate is.
2. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S1 , the size of the thick film ceramic substrate is 2×2 mm.
3. The method for evaluating the reliability of a ceramic substrate welding process according to claim 1, characterized in that: In step S1, the pad pattern is a regular pattern, which includes but is not limited to a rectangle, a regular hexagon and a circle.
4. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S1, the steel shell includes but is not limited to No. 10 steel or Kovar alloy.
5. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S1, the thick film ceramic substrate is welded to the steel housing in a welding method including but not limited to hot plate reflow welding and vacuum reflow welding.
6. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S1 , the number of unitized ceramic welded substrate samples is greater than 30.
7. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S2, the number of samples for testing shear strength and fracture surface porosity is greater than 5.
8. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S3, the high temperature baking condition is to place the sample in an environment with a temperature greater than 70% of the melting point of the solder and bake it at a high temperature for 30-168 hours.
9. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S3, the number of samples subjected to high temperature storage is greater than 5.
10. The ceramic substrate welding process reliability evaluation method according to claim 1, characterized in that: In step S4, at least 5 samples are subjected to temperature cycle aging test at each temperature.
Citation Information
Cited By
A vibration reliability design method and system for a component interconnection process
CN122595968A